INDIKASI PERSALINAN SECTIO CAESAREA BERDASARKAN UMUR DAN PARITAS - Arimina Hartati Pontoh (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Sectio caesarea is an attempt to give birth to the fetus through surgery in the abdomen by cutting the uterine wall. Data obtained at Gubeng Pojok Surabaya DKT Hospital found that the incidence of sectio caesarea tended to increase from 2012 - 2013 by 3.23% and in 2013 - 2014 by 0.93%. The purpose of this study will be to describe the indications of caesarean section delivery based on maternal age and parity in the DKT Hospital of Gubeng Pojok Surabaya in 2016 Method: This study uses descriptive method. The study population was all mothers giving birth with setio caesarea in DKT Hospital Gubeng Pojok Surabaya in 2016 as many as 459 people. Sampling by non probability sampling with saturated sampling technique amounted to 459 people. Then a frequency tabulation and cross tabulation were made. Results: The results of the study were as follows: Caesarean section with an indication of 58.17% while non-indicative sectio caesarea was 41.83%. The majority of sectio caesarea occurs at the age of 20 - 35 years as much as 82.35% with the majority of multiparous parity as much as 57.74%. Discussion: With the high incidence of sectio caesarea, counseling is needed on the importance of reproductive health in pregnancy and early detection to deal with the occurrence of complications so that regular prenatal care is needed.